The Integration of Elderly and Disabled People into Urban and Social Life: A New Model for Konya/Turkey-YEBAM - H.Filiz Alkan Meshur; Ahmet Alkan (European Regional Science Association (ERSA), 2014)
The process of demographic change occurring around the world is also reflected in Turkey. The elderly population and thus, the number of people who are in need of care, will increase in Turkey in the future. Furthermore, approximately 13% of Turkey's population consists of disabled people. This ratio reaches 20% when including disabilities caused by aging. Certain physical and mental disabilities due to aging make the lives of elderly people more difficult. Strengthening the connection of elderly and disabled people with life and society can only be possible by providing them with environments to spend their lives in a safe, healthy, independent and productive manner. It is not possible to solve this problem with the previous care models in Turkey. Environments that combine working, education and social possibilities, providing the elderly and disabled people with independent living areas, should be created. Despite prominent developments in recent years for the education of disabled people, they have not yet reached the desired level in social and professional areas. Therefore, there is an urgent need for a comprehensive training, research and care center for elderly and disabled people (YEBAM) that will provide a combination of care, rehabilitation, educational, social and cultural services. The purpose of this paper is to evaluate YEBAM, which will be the first center in Turkey providing education, care and job opportunities for elderly and disabled people, in social and spatial terms. The first section discusses the process of demographic change around the world and in Turkey and the search for new ways of care and design. The next section discusses the purpose, vision, regional and national importance, design concept and principles of YEBAM. YEBAM's layout plan and architectural plans were prepared taking social, psychological and spatial needs of elderly and disabled people in light of universal design principles. In this plan, elderly and disabled people will have the chance to live in their own houses and will take part in social activities in common areas. The care services required will be provided by trained personnel.
Keywords: 330; Elderly; disability; disabled people; elderly people; training research and care center